LAW OF SUBSTANCE AND CONSISTENCY OF REGIONAL REGULATION NUMBER 3 OF 2006 CONCERNING COMMUNITY DEVELOPMENT ACTIVITIES IN KARIMAH - Anwar Anwar (UIN Sunan Gunung Djati Bandung, 2019)
Laying Islamic Sharia as an agenda of local government is also quite common among the people. Various institutions and activities aimed at campaigning for the